Soda Intake Is Directly Associated with Serum C-Reactive Protein Concentration in Mexican Women. Issue 1 (25th January 2018) - Tamez, Martha; Monge, Adriana; López-Ridaura, Ruy; Fagherazzi, Guy; Rinaldi, Sabina; Ortiz-Panozo, Eduardo; Yunes, Elsa; Romieu, Isabelle; Lajous, Martin
Abstract: Background: Soda intake is associated with an increased risk of cardiovascular disease. Consumption of diet sodas, often considered healthy alternatives to sodas, could also increase the likelihood of cardiovascular outcomes. Objective: This study aims to evaluate the relation between soda and diet soda and biomarkers of cardiovascular risk. Methods: We conducted a cross-sectional analysis among 825 Mexican women free of diabetes, cardiovascular disease, and cancer, and for whom serum concentrations of C-reactive protein (CRP), C-peptide, adiponectin, and leptin were available. Mean ± SD age was 45.9 ± 6.6 y, the majority of women were premenopausal (60.4%), and the prevalence of obesity was 35%. We estimated the adjusted percentage differences in biomarkers and 95% CIs by performing multiple linear regression models comparing categories of consumption for soda and diet soda adjusting for age, family history of heart disease, menopause, menopausal hormone therapy, socioeconomic status, region, smoking, physical activity, alcohol intake, and dietary patterns. Results: In the entire study sample we observed a 50% higher serum CRP concentration in women in the highest soda intake quartile (median intake: 202.9 mL/d, IQR: 101.4, 304.3 mL/d) compared to those in the lowest (median intake: 11.8 mL/d, IQR: 0.0, 152.1 mL/d). After stratification by menopausal status, results remained significant only for premenopausal women. Premenopausal women in the highest quartile of soda intake had 56% higher CRP concentration relative to women in the lowest quartile. We observed no significant association with the other biomarkers. After further adjustment for body mass index, a potential mediator, results remained significant only for CRP. Diet soda consumption was not associated with any of the biomarkers. Conclusions: Consumption of soda was associated with adverse levels in a biomarker of inflammation and cardiovascular risk, serum CRP, in Mexican women. These results add to the accumulating evidence on soda and cardiovascular risk. More research is necessary to understand the potential impact of artificially sweetened sodas.